Disease threats to tigers and their prey - Gilbert, Martin; Dvornicky-Raymond, Zachary; Bodgener, Jessica (Frontiers in Ecology and Evolution, 2023)
The contraction of the global tiger population over the last 100 years into small, often isolated subpopulations has made them increasingly vulnerable to the impact of disease. Despite this, the health of wild tigers continues to be under-funded and explored. Even a pathogen like canine distemper virus (CDV), which has been associated with localized declines and increases the likelihood of population extinction, has received little research attention in most tiger range countries. The emergence of new threats has posed fresh challenges, including African swine fever (ASF), which has the potential to devastate wild boar populations, and severe acute respiratory syndrome coronavirus (SARS-CoV2) with implications for tiger conservation that remain unknown. The objective of this review is to synthesize current research on the health of tigers and their prey that impacts the conservation of tigers in the wild. Published sources are interpreted based on three mechanisms through which disease can affect the viability of tiger populations: 1) by reducing the survival of adult tigers, 2) by reducing breeding productivity, and 3) by reducing the carrying capacity of tiger habitat through decreased prey abundance. Examples of CDV, SARS-CoV2, carnivore protoparvovirus 1 and ASF are used to illustrate these processes and inform discussion of research and mitigation priorities.